Efficient time splitting schemes for the monodomain equation in cardiac electrophysiology. (2nd January 2023) - Lindner, Laura P.; Gerach, Tobias; Jahnke, Tobias; Loewe, Axel; Weiss, Daniel; Wieners, Christian
Abstract: Approximating the fast dynamics of depolarization waves in the human heart described by the monodomain model is numerically challenging. Splitting methods for the PDE‐ODE coupling enable the computation with very fine space and time discretizations. Here, we compare different splitting approaches regarding convergence, accuracy, and efficiency. Simulations were performed for a benchmark problem with the Beeler–Reuter cell model on a truncated ellipsoid approximating the left ventricle including a localized stimulation. For this configuration, we provide a reference solution for the transmembrane potential. We found a semi‐implicit approach with state variable interpolation to be the most efficient scheme. The results are transferred to a more physiological setup using a bi‐ventricular domain with a complex external stimulation pattern to evaluate the accuracy of the activation time for different resolutions in space and time.